Comparison of CrN Coatings Prepared Using High-Power Impulse Magnetron Sputtering and Direct Current Magnetron Sputtering - Bai, Heda; Li, Jin; Gao, Jialai; Ni, Jinyang; Bai, Yaxiong; Jian, Jie; Zhao, Lin; Bai, Bowen; Cai, Zeyun; He, Jianchao; Chen, Hongsheng; Leng, Xuesong; et al. (Materials, 2023)
Chromium Nitride (CrN) coatings have widespread utilization across numerous industrial applications, primarily attributed to their excellent properties. Among the different methods for CrN coating synthesis, direct current magnetron sputtering (DCMS) has been the dominant technique applied. Nonetheless, with the expanded applications of CrN coatings, the need for enhanced mechanical performance is concurrently escalating. High-power impulse magnetron sputtering (HiPIMS), an innovative coating deposition approach developed over the past three decades, is gaining recognition for its capability of yielding coatings with superior mechanical attributes, thereby drawing significant research interest. Considering that the mechanical performance of a coating is fundamentally governed by its microstructural properties, a comprehensive review of CrN coatings fabricated through both techniques is presented. This review of recent literature aims to embark on an insightful comparison between DCMS and HiPIMS, followed by an examination of the microstructure of CrN coatings fabricated via both techniques. Furthermore, the exploration of the underlying factors contributing to the disparities in mechanical properties observed in CrN coatings is revealed. An assessment of the advantages and potential shortcomings of HiPIMS is discussed, offering insight into CrN coating fabrication.